The Known, the New, and a Possible Surprise: A Re-Evaluation of the Nucleomorph-Encoded Proteome of Cryptophytes. (24th May 2019) - Zauner, Stefan; Heimerl, Thomas; Moog, Daniel; Maier, Uwe G
Abstract: Nucleomorphs are small nuclei that evolved from the nucleus of former eukaryotic endosymbionts of cryptophytes and chlorarachniophytes. These enigmatic organelles reside in their complex plastids and harbor the smallest and most compacted eukaryotic genomes investigated so far. Although the coding capacity of the nucleomorph genomes is small, a significant percentage of the encoded proteins (predicted nucleomorph-encoded proteins, pNMPs) is still not functionally annotated. We have analyzed pNMPs with unknown functions via Phyre 2, a bioinformatic tool for prediction and modeling of protein structure, resulting in a functional annotation of 215 pNMPs out of 826 uncharacterized open reading frames of cryptophytes. The newly annotated proteins are predicted to participate in nucleomorph-specific functions such as chromosome organization and expression, as well as in modification and degradation of nucleomorph-encoded proteins. Additionally, we have functionally assigned nucleomorph-encoded, putatively plastid-targeted proteins among the reinvestigated pNMPs. Hints for a putative function in the periplastid compartment, the cytoplasm surrounding the nucleomorphs, emerge from the identification of pNMPs that might be homologs of endomembrane system-related proteins. These proteins are discussed in respect to their putative functions.